2018
DOI: 10.1002/pola.29049
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of superhydrophobic and oleophobic surfaces via the combination of Cu(0)‐mediated reversible‐deactivation radical polymerization and click chemistry

Abstract: The fabrication of novel hydrophobic, superhydrophobic, and oleophobic surfaces on glass using nanosilica particles modified with polymer brushes prepared via surface initiated Cu(0)‐mediated reversible‐deactivation radical polymerization was demonstrated. Monomers including n‐butyl acrylate, 2,2,2‐trifluoroethyl methacrylate, and 1,1,1,3,3,3‐hexafluoroisopropyl acrylate were used to synthesize a series of nanosilica–polymer organic/inorganic hybrid materials. Products were analyzed using infrared spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…After fluorination, a significant weight loss of pHEMA-F15 between 283 °C and 454 °C was due to the decomposition of the pHEMA substrate. The first weight loss of pHEMA-F15 started from 191 °C, which indicated that the thermal stability of pHEMA-F15 was decreased compared to pHEMA. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After fluorination, a significant weight loss of pHEMA-F15 between 283 °C and 454 °C was due to the decomposition of the pHEMA substrate. The first weight loss of pHEMA-F15 started from 191 °C, which indicated that the thermal stability of pHEMA-F15 was decreased compared to pHEMA. , …”
Section: Resultsmentioning
confidence: 99%
“…The first weight loss of pHEMA-F15 started from 191 °C, which indicated that the thermal stability of pHEMA-F15 was decreased compared to pHEMA. 51,52 Surface Energy and Wettability. To further investigate the effects of surface fluorination, static contact angles of water and CH 2 I 2 on the original and fluorinated membranes were measured.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…Figure shows the weight loss curve of bare NP, Br-NP, and PCH-NP as a function of temperature. The weight percentages of the immobilized initiator and grafted polymer brushes were determined to be 4 and 60 wt %, respectively. , According to the product information provided by Sigma-Aldrich, the density of NP is 2.2 g/cm 3 and the size is 20 nm. The grafting density (ρ) was calculated by the following equation: …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the weight loss curve of bare NP, Br-NP, and PCH-NP as a function of temperature. The weight percentages of the immobilized initiator and grafted polymer brushes were determined to be 4 and 60 wt %, respectively. , According to the product information provided by Sigma-Aldrich, the density of NP is 2.2 g/cm 3 and the size is 20 nm. The grafting density (ρ) was calculated by the following equation: ρ = normalw normalt % normalp normalo normall normaly normalm normale normalr normalw normalt % normalN normalP normals D normalN normalP normals italicV normalN normalP normals N normalA M W 4 π r N P s 2 …”
Section: Resultsmentioning
confidence: 99%
“…The surface-initiated polymerization protocol used here was based on a method developed by Enayati and Abbaspourrad. , First, 1 g unmodified amaranth starch was dispersed in 100 mL of acetonitrile (instead of water) in a beaker and sonicated for 15 min. Then, the beaker and its contents were heated in a water bath set at 60 °C [Figure A(i)].…”
Section: Methodsmentioning
confidence: 99%